2012
DOI: 10.2340/16501977-0946
|View full text |Cite
|
Sign up to set email alerts
|

Anti-spastic effects of the direct application of vibratory stimuli to the spastic muscles of hemiplegic limbs in post-stroke patients: A proof-of-principle study

Abstract: The direct application of vibratory stimuli has anti-spastic effects in the hemiplegic upper limbs of post-stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 0 publications
3
83
0
3
Order By: Relevance
“…550 Vibration applied to spastic muscle groups might be considered to reduce spasticity transiently, but it is not effective for long-term reduction of spastic hypertonia. [551][552][553] Injection of botulinum toxin is used commonly to treat upper limb spasticity in patients with stroke and is recommended in several recent review articles and previously published guidelines as an important tool in the comprehensive management of poststroke spastic hypertonia. 149,[554][555][556][557] Injections of botulinum toxin A can reduce spasticity significantly as measured by the Ashworth scale.…”
Section: Spasticitymentioning
confidence: 99%
“…550 Vibration applied to spastic muscle groups might be considered to reduce spasticity transiently, but it is not effective for long-term reduction of spastic hypertonia. [551][552][553] Injection of botulinum toxin is used commonly to treat upper limb spasticity in patients with stroke and is recommended in several recent review articles and previously published guidelines as an important tool in the comprehensive management of poststroke spastic hypertonia. 149,[554][555][556][557] Injections of botulinum toxin A can reduce spasticity significantly as measured by the Ashworth scale.…”
Section: Spasticitymentioning
confidence: 99%
“…The vibration location varied in previous studies that reported a positive effect of vibration on spasticity and related functional impairment. Noma et al [12,19] reported that vibration to the volar side of the fingers, palm, wrist flexor tendon, and muscle belly of the biceps brachii had antispastic effects in the hemiplegic upper limbs of stroke patients. Marconi et al [13,20] suggested that muscle belly stimulation of the flexor carpi radialis and biceps brachii resulted in improving spasticity and motor function with a parallel change in intracortical inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Vibratory stimulation is a strong proprioceptive stimulus and can reach both the primary somatosensory and motor cortices [37,38,39] and change the intracortical inhibitory circuit [40]. Several studies proposed that the vibration in patients with spasticity can lead to the redistribution of intracortical synapses related to supraspinal motoneuron excitability control, and the effects would be correlated with long-term functional improvement [17,18,19,20]. Vibration can also mechanically mobilize the muscle and connective tissue to alleviate stiffness and contracture.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure of applying the vibratory stimulator was that the biceps brachii and flexor carpi radialis in the affected side were placed on the heads of the vibratory stimulators and tied together by straps. Two kg of weights were put on the neck portion of the vibratory stimulators to fix the location of stimulation during the operation9 ) . Box and block test (BBT) was used for hand dexterity.…”
Section: Methodsmentioning
confidence: 99%